PEMANFAATAN TEPUNG MAGGOT (Hermetia illucens) DIFERMENTASI MENGGUNAKAN Aspergillus niger DALAM PAKAN UNTUK PERTUMBUHAN BENIH IKAN GURAMI (Osphronemus goramy) - Romadhan, Wahyu; Adelina, Adelina; Suharman, Indra (Journal of Fish Nutrition, 2025)
This study evaluated the utilization of maggot flour fermented with Aspergillus niger in gourami fish seed feed. The research was conducted using a one-factor Complete Random Design (RAL) with five treatments and three replications. The treatment used was feed without fermented maggot flour (P0), feed containing 25% fermented maggot flour (P1), feed containing 50% fermented maggot flour (P2), feed containing 75% fermented maggot flour (P3), and 100% feed containing fermented maggot flour (P4). Fish with an average initial weight of 2.93 ± 4.00 g were stocked into 15 net cages (1 × 1 × 1 m³) at a density of 25 fish per cage. The fish were fed test feeds at 10% of their body weight, 3 times daily (08:00, 13:00, and 17:00), for 56 days. Feed digestibility was assessed in an aquarium (60 × 40 × 40 cm³) at a dense stocking density of 10 fish per m³. The test feed contained 0,5 % Cr2O3. The results indicated that the inclusion of 75% fermented maggot meal yielded the best outcomes, with feed digestibility of 74.36%, protein digestibility of 88.76%, feed efficiency of 46.10%, protein retention of 33.38%, specific growth rate of 3.29% per day, and a survival rate of 100%.